Acquired Bilateral Peripheral Vestibular System Impairment: Rehabilitative Options and Potential Outcomes - Calder, Jaynee H.; Jacobson, Gary P. (Journal of the American Academy of Audiology, 2000)
Acquired bilateral vestibular impairment can be a devastating disorder that is most frequently the result of aminoglycoside-induced toxicity. The presenting complaints are typically oscillopsia and gait and balance disturbances. These patients can be excellent candidates for vestibular rehabilitation therapy that focuses on facilitating maximal use of any remaining vestibular function, improving gaze and postural stability through the use of visual and somatosensory cues, and improving home and workplace safety. The prognosis for recovery is determined by the extent of the loss and the presence of other progressive disorders that may affect vision or somatosensation, coexisting illnesses, and the patient's compliance with the therapy program. Two cases are presented to illustrate the salient aspects of vestibular rehabilitation for patients with acquired bilateral vestibular system loss, including factors affecting patient progress and final outcome.Abbreviations: COR = cervico-ocular reflex, DHI = Dizziness Handicap Inventory, ENG = electronystagmography, IV = intravenous, VOR = vestibulo-ocular reflex
Keywords: Imbalance; oscillopsia; rehabilitation; unsteadiness; vestibular